Improving the Students’ Reading Comprehension by Using Magazine at the First Grade Students of SMPN 2 Lasusua - Nur Hijrah (Journal of Teaching and Education, 2022)
This research was aimed to improved of students’ comprehension in reading comprehension by using magazine. The subject of this research was 26 students of the first grade students of SMPN 2 Lasusua . The researcher applied classroom action research which has conducted into two cycles.The finding showed that the students’ reading comprehension indicated the significant increase from the average score of reading comprehension within the two cycles (cycle 1 and 2). In average score of test, the achievement score was 61.1 for cycle 1 and 83.3 for cycle 2. From these results, this research indicated that magazine can improve the students’ reading comprehension in teaching and learning process, particularly on the aspect of finding the main ideas.